Strategic Forecasting of Electricity Demand Using System Dynamics Approach - Salman Ahmad, Akhwanzada; Razman, Mat Tahar (IACSIT Press, 2012)
Electricity has become an important source of energy in human society. The enormous use of electricity necessitates a mechanism to predict the future demand. Forecasting models provide that mechanism. They facilitate decision makers in keeping a balance between supply and demand, thus strategically managing the supply system A simulation based on system dynamics methodology is developed for demand forecasting. The variables used are population and per capita consumption of electricity to forecast electricity demand. The forecasting horizon of the model is 11 years from 2011 to 2022. Malaysia is used as a case study. The simulation model estimates that at the current rate of consumption and population growth there will be a need of 151.05 terawatt-hour of electric energy in year 2022. It is found that that by using simulation, a fairly accurate forecast can be obtained.